Analisis Loyalitas Donatur dan Brand Trust: Studi pada YDSF Al-Falah Surabaya - Mohamad Yusak Anshori; Denis Fidita Karya; Azrida Ayu Rahmania; Rizki Amalia Elfita (Journal of Management and Business Review, 2022)
In the last decade, the movement of the business and social world, especially the National Amil Zakat Agency (BAZNAS), has experienced rapid environmental changes. Rapid environmental changes require an institution to try to run its work program to continue to grow and develop so that its income does not decrease and can still achieve the predetermined target. If the institution can deal with environmental developments and competition quickly, then the institution will be successful. This study analyzes the effect of brand image, service quality, and donor religious commitment on brand trust and donor loyalty. The research method uses quantitative methods with a purposive sampling technique. The questionnaires were distributed through email and WhatsApp using a google form, which was distributed to 182 respondents within two weeks. The analysis in this study uses Partial Least Square (PLS). The results of this study are that there is a positive influence between brand image, service quality, and donor religious commitment to brand trust. Furthermore, brand image, service quality, and donor religious commitment positively influence donor loyalty